2008
DOI: 10.1016/j.dnarep.2008.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Widespread distribution of DNA glycosylases removing oxidative DNA lesions in human and rodent brains

Abstract: High metabolic activity and low levels of antioxidant enzymes make neurons particularly prone to damage by reactive oxygen species. Thus, repair of oxidative DNA damage is essential for normal brain function. Base excision repair is the major pathway for repair of oxidative DNA damage, and is initiated by DNA glycosylases recognizing and removing the damaged base. In mammalian cells at least five different DNA glycosylases with overlapping substrate specificity, NEIL1, NEIL2, NEIL3, OGG1 and NTH1, remove oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
77
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 53 publications
3
77
0
Order By: Relevance
“…and NEIL1 (Nei-like DNA glycosylase 1) 68 . Some repair ability has been reported also for NEIL3 69,70 , which is otherwise suggested to be more important for neurogenesis than for classical DNA repair [71][72][73][74] . The mechanisms for regulation of base excision repair after neuronal injury are not well understood.…”
Section: Energy Failure Calcium Overload and Excitotoxicitymentioning
confidence: 99%
“…and NEIL1 (Nei-like DNA glycosylase 1) 68 . Some repair ability has been reported also for NEIL3 69,70 , which is otherwise suggested to be more important for neurogenesis than for classical DNA repair [71][72][73][74] . The mechanisms for regulation of base excision repair after neuronal injury are not well understood.…”
Section: Energy Failure Calcium Overload and Excitotoxicitymentioning
confidence: 99%
“…Repair of AP sites, which are highly mutagenic and cytotoxic because DNA replication can result in either double strand breaks or misincorporations, starts with the actions of an AP endonuclease (6). DNA glycosylases show widespread but differential expression, presence, and incision activity, suggesting important age dependent roles both in brain (15) and liver tissue (16).…”
mentioning
confidence: 99%
“…[25] In the human brain, NEIL2 showed a widespread expression pattern in accordance with OGG1, NTH1, and NEIL1. [24] Rolseth et al [24] also found that NEIIL2 had a similar expression pattern as NEIL1 by detecting expression of NEIL2 in mouse brain during postnatal development, but with a slightly increased expression with age. In summary, NEIL2 has a widespread expression pattern in human and rodent and the subcellular localization of NEIL2 is in mitochondria and in the nucleus.…”
Section: Neil2 Expression Patternsmentioning
confidence: 94%
“…In the central nervous system, NEIL3 mRNA expression has been investigated in different brain areas of human adults by Northern blot hybridization. [24] NEIL3 could not be detected in any brain region of adult humans. In contrast, by studying the expression of NEIL3 in mouse brain during postnatal development, NEIL3 transcripts can be observed in the subventricular zone (SVZ), hilus of the hippocampal formation, the rostral migratory stream, and the Purkinje cell of the cerebellum in P3 mice brain.…”
Section: Neil3 Expression Patternsmentioning
confidence: 99%
See 1 more Smart Citation